FETISISME KOMODITI DAN MISTIFIKASI DALAM IKLAN - Muzairi Muzairi (UIN Sunan Kalijaga Yogyakarta, 2014)
Fetisyism of commodity is a phenomenon in which someone sees the meaning of something as inherent part of its physical existence, but actually the meaning is just created through its integration into system of meaning. As Marx says, fetisyism of commodity is phenomena, that is, seeing something as having an inherent value in it, whereas, the value is made by man. The Marx's analysis is very important in our understanding of how a product or commodity communicate a social relation (class, status, condition, role, grade, prestige) operating in a social context. Marx uses term mystification to explain false appearance or false meaning of a commodity, that actually have had a certain meaning in society.